NEW DATA ON THE MIDDLE MIOCENE BIOSTRATIGRAPHY (NANNOFOSSILS, MOLLUSKS) AND LITHOLOGY OF THE TAMANSKII PENINSULA AND WESTERN CISCAUCASIA - Golovina L.A.; Goncharova I.A.; Rostovtseva Yu.V. (My University, 2004)
Lithology and distribution of nannofossils and mollusks in two continuous sections (anticline of the Mt. Zelenskii, Tamanskii Peninsula, and the Pshekha River section, Western Ciscaucasia) of the upper Chokrakian-lower Sarmatian deep-water sediments have been studied. Sediments in the Mt. Zelenskii anticline core are dated back to the late Chokrakian based on molluscan records. In the interval of the upper Konkianlowermost Sarmatian, there is recorded flourishing of the monothetic Reticulofenestra pseudoumbilica assemblage. In the studied sections, the upper boundary of the Konkian Horizon is suggested to be at the top of the marker bed with abundant Reticulofenestra pseudoumbilica Gartner, and the lower boundary is placed at the first occurrence level of polyhaline benthic or planktonic fossils. The first occurrence of Abra reflexa (Eichw.) can be regarded as indicative of the Konkian level in the deep-water sediments barren of mollusks. The general lithologic trend and analyzed fauna are used to elucidate the sedimentation regime during the late Chokrakian-middle Sarmatian and to reconstruct hydrologic peculiarities of the basin at that time. Accumulation of fine-grained peloid (cyanobiontic) limestones took place in deeper parts of the basin during the late Chokrakian-Karaganian, when the marine water circulation was disturbed. Algal sediments intensively accumulated parallel to clay sedimentation in shoal settings and likely in the entire euphotic zone of the basin.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен